Maternal-Cord Blood Vitamin D Correlations Vary by Maternal Levels - Ganesa Wegienka; Hareena Kaur; Roopina Sangha; Andrea E. Cassidy-Bushrow (Journal of Pregnancy)
Vitamin D levels of pregnant women and their neonates tend to be related; however, it is unknown whether there are any subgroups in which they are not related. 25-Hydroxyvitamin D [25(OH)D] was measured in prenatal maternal and child cord blood samples of participants (n=241 pairs) in a birth cohort. Spearman correlations were examined within subgroups defined by prenatal and delivery factors. Cord blood as a percentage of prenatal 25(OH)D level was calculated and characteristics compared between those who did and did not have ≥25% and ≥50% of the maternal level and those who did and did not have a detectable 25(OH)D level. The correlation among Black children was lower than in White children. When the maternal 25(OH)D level was <15 ng/mL, the overall correlation was r=0.16. Most children had a 25(OH)D cord blood level less than half of their mother’s; 15.4% had a level that was <25% of their mother’s. Winter birth and maternal level were associated with the level being less than 25%. Children with undetectable levels were more likely to be Black and less likely to be firstborn. These data suggest mothers may reduce their contribution to the fetus’s 25(OH)D supply once their own level becomes low.